ANALYSIS ON STRESS AND DEFORMATION OF STEEL WIRE ROPE AT WR-CVT DISCONTINUOUS CONTACT WIRE - MA LiYun; QIU YanEr; YANG Yun (Jixie qiangdu, 2018)
Aiming at the wear problem of the new-type metal belt type continuously variable transmission steel rope ring,the discontinuous contact geometry model and the finite element analysis model of the steel rope ring and the metal block in the WR-CVT transmission process are established,and the metal block and the steel rope ring are analyzed. The geometrical contact position and its stress and deformation; the results show that: the wire with the rope groove edge stress concentration,the maximum stress of steel wire is 1 273 MPa,the stress value is greater than the other strand wire stress,in the rope groove nonedge contact,The stress distribution of the wire in the strand is even and the maximum stress is 745. 6 MPa. The maximum difference between the steel wire is 0. 028 mm. The deformation of the wire in the strand is extremely poor,and the deformation of the steel wire loop and the steel wire in different sections is not uniform. Therefore,the wear of the steel rope ring at the discrete part of the bending section of the pulley is relatively serious,and it is relatively easy to malfunction when in the working state.